PENGARUH LUBANG DAN EKSENTRISITAS TERHADAP KUAT TEKAN BETON - Agustiar, Agustiar (Jurusan Teknik Sipil Universitas Tadulako, 2014)
The use of hollow concrete in buildings is allowed. It is accordingly to SNI 03-2847-2002, which mentioned that pipeline with its holes that are embedded in column should not occupy more than 4% of cross-section area of the column. The use of holes in the column is used for plumbing or electrical installations. Reduction of cross-sectional area of concrete causes the concrete strength to bear axial load will also be reduced. Besides that, in the installation of pipes in a column, they could be in inclined position, which could result in an eccentricity to the gravity centre of column. Â Based on the problem, this research aims to find out the effect of eccentricity on the concrete column with hole to its strength in supporting axial load. Â There were 56 cylindrical specimens with 15 cm of diameter and 30 cm of high used in this research. The results showed that the hole in concrete resulted in reducing of the compressive strength of concrete. The reducing in strength is expected to be due to reducing in cross-section area of concrete. The use of holes up to 3.8% of the concrete cross-section area results in reducing the strength of concrete up to 16.86% (BN2) of the strength of concrete without holes. The reduction in strength due to the holes eccentricity of 2 and 3 cm to the eccentricity of concrete, were 24.64 and 25.36% respectively to the concrete strength without hole. Then the strength of concrete at 3.8% aperture area still meets the requirements. Based on that also why the hole bounded by SNI 03-2847-2002, pasal 8.3 (4) can still be used by 4%. Keywords: concrete, eccentricity, hole, compressive strength.